The characterization, pathotype distribution and genetic diversity of Xanthomonas oryzae pv. oryzae in rice production centers of the Special Region of Yogyakarta, Indonesia - Arwiyanto, Triwidodo; Sulandari, Sri; Irpawa, Dea Musytari Intan (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
Xanthomonas oryzae pv. oryzae (Xoo) is a pathogenic bacterium that induces bacterial leaf blight in rice. This disease is challenging to treat due to the presence of multiple pathotypes that can harm the plants. Characterizing and determining the distribution of pathotypes and genetic diversity of Xoo in the Special Region of Yogyakarta is essential for evaluating the appropriate approach to managing rice leaf blight in different districts of Yogyakarta. This study aimed to ascertain the characterization, distribution of pathotypes, and genetic diversity of Xoo in the Special Region of Yogyakarta. This study involved the isolation and characterization of Xoo from various rice production centers in Yogyakarta. The distribution of Xoo pathotypes was determined using five differential varieties (Tetep (4251), PB 5 (4827), Java 14 (11022), Kencana Bali (4477), and Kuntulan (1529)). Pathogenicity testing was conducted on six common varieties used by Yogyakarta farmers (IR64, Ciherang, C4, Mekongga, Menthik Wangi, and Inpari 42). Additionally, molecular characterization of Xoo was performed. The bacterial leaf blight that affects rice plants in the Yogyakarta region, caused by Xoo, is identified by yellow circular colonies. It exhibits a negative Gram staining response, positive catalase activity, negative oxidase activity, and does not hydrolyse starch. The Xoo pathotypes identified in Yogyakarta are IV, VIII, and XI. All six prevalent cultivars utilized by farmers in Yogyakarta are susceptible to Xoo. Out of each pathotype, four isolates were chosen, and they were divided into two distinct groups based on the DNA banding pattern they formed. Among these isolates, three had the lowest base sequence at 200 bp, while one isolate had a different DNA banding pattern with the lowest base sequence between 250–300 bp.